New taxa and notes on some Landrevinae (Orthoptera: Gryllidae) from Malay Peninsula - Tan, Ming Kai; Kamaruddin, Khairul Nizam (Zootaxa, 2016)
Here, taxonomic notes on species from three genera of bark crickets are presented. A new locality is recorded for Duolandrevus (Bejorama) parvulus Gorochov, 2016: Singapore. Two new species of Landrevinae are described: one species of Endodrelanva Gorochov, 1999 from Singapore: Endodrelanva jimini sp. nov.; one species of Odontogryllodes Chopard, 1969 from Fraser’s Hill, Peninsular Malaysia: Odontogryllodes gratus sp. nov. The male of Odontogryllodes latus Chopard, 1969 is also described for the first time and female is redescribed. Keys to all known species of Endodrelanva and Odontogryllodes is provided.